Beyond the Halal Seal: Maqâshid al-Syarî‘ah Content Marketing and Customer Engagement in Halal Small and Medium Enterprises - Ahmad Dumyathi Bashori; Suhendra Suhendra; Sucayono Sucayono (Madania: Jurnal Kajian Keislaman, 2026)
This research tries to examine whether the marketing value that is owned by halal small and medium enterprises (SMEs) does not stop at the certification seal but rather moves toward the substance of the content that such firms publish on social media. By departing from customer engagement theory and also from the higher objectives of Islamic law (maqâshid al-syarî‘ah), this study tests how four drivers at the content level, namely halal content authenticity, Islamic content quality, maqâshid al-syarî‘ah content implementation, and trust toward halal social media content, give effect to customer engagement. The data in this research were collected from customers who follow the accounts of halal SMEs on social media, and the analysis itself was carried out through partial least squares structural equation modelling with the SEMinR package, together with 1,000 bootstrap resamples. As for the measurement model, its internal consistency and its convergent validity were proven to be adequate, whereas the discriminant validity among the constructs, which are strongly correlated with one another, is still examined and is marked for further confirmation. The structural model was able to explain a fairly large portion of the variance in customer engagement (R² = 0.754), and all four hypotheses in this study were supported. Among the four of them, trust toward halal social media content gave the strongest effect, and it was then followed quite closely by Islamic content quality and by halal content authenticity, while maqâshid al-syarî‘ah content implementation still contributed a significant effect even though it was more modest. Based on such findings halal certification only works as a threshold cue and not as a relational cue, so that engagement is in fact built through content that can be trusted, that is correct from the religious side, and that stands on ethics. Therefore, this study contributes an integrative reading, which is based on maqâshid, upon halal content marketing, and at the same time it also gives practical direction for the owners of SMEs who compete within crowded digital marketplaces. Penelitian ini berusaha menelaah apakah nilai pemasaran yang dimiliki oleh usaha kecil dan menengah (UKM) halal sesungguhnya tidak berhenti pada label sertifikasi, melainkan justru bergerak menuju substansi konten yang mereka publikasikan di media sosial. Dengan berpijak pada teori keterlibatan pelanggan dan juga pada tujuan tertinggi hukum Islam (maqâshid al-syarî‘ah), penelitian ini menguji bagaimana empat pendorong pada tingkat konten, yakni autentisitas konten halal, kualitas konten Islami, implementasi konten maqâshid al-syarî‘ah, serta kepercayaan terhadap konten halal di media sosial, memberikan pengaruh terhadap keterlibatan pelanggan. Data dalam penelitian ini dihimpun dari pelanggan yang mengikuti akun UKM halal di media sosial, dan analisisnya sendiri dilakukan melalui pemodelan persamaan struktural berbasis partial least squares dengan paket SEMinR beserta 1.000 resampel bootstrap. Adapun untuk model pengukuran, konsistensi internal dan validitas konvergennya terbukti memadai, sedangkan validitas diskriminan di antara konstruk yang saling berkorelasi kuat masih dikaji dan ditandai untuk dikonfirmasi lebih lanjut. Model struktural mampu menjelaskan bagian yang cukup besar dari varians keterlibatan pelanggan (R² = 0,754), dan keempat hipotesis dalam penelitian ini pun terdukung. Di antara keempatnya, kepercayaan terhadap konten halal di media sosial memberikan pengaruh yang paling kuat, yang kemudian diikuti secara cukup dekat oleh kualitas konten Islami dan oleh autentisitas konten halal, sementara implementasi konten Maqashid Syariah tetap menyumbang pengaruh yang signifikan walaupun lebih moderat. Berdasarkan temuan yang demikian dapat dilihat bahwa sertifikasi halal hanya bekerja sebagai isyarat ambang dan bukan sebagai isyarat relasional, sehingga keterlibatan pada kenyataannya dibangun melalui konten yang dapat dipercaya, yang benar dari sisi keagamaan, serta yang berpijak pada etika. Oleh karena itu, penelitian ini menyumbangkan sebuah pembacaan yang integratif, yang berbasis maqâshid, atas pemasaran konten halal, dan sekaligus juga memberikan arahan praktis bagi para pemilik UKM yang bersaing di dalam pasar digital yang padat.